COMPASS collaborative research Strand 1: assessment. (1st April 2011) - Stark, D; Bennett, M; Johnson, B; Murray, S A; Rainey, P; Rayner, L; Gao, W; Higginson, I J
Abstract : Abstract: Introduction and aims: Strand 1 develops assessment and outcome measures for use and intervention in research and clinical practice. We set out to improve the patient assessment platform, to improve comparable measurement within and between studies. Methods: Our process of meeting, rigorous collaborative discussion, guidance for researchers in training, grant application and dissemination has brought integration of service user involvement and collaboration among the different universities. We focused upon symptoms including psychological distress care giver burden and palliative outcomes. We evaluated measures from diagnosis to survivorship and end of life care. Results: We have recently published about measures of psychological distress across cancer trajectories, clinical and psychometrics features of the General Health Questionnaire across the cancer trajectory, complex interventions for cancer survivors and assessment of care giver burden. In our collaborative's evolution, we continue to work on psychological distress assessment across cancers, characteristics of psychological distress, political challenges to supportive and palliative care research, cancer pain, palliative outcomes, short-form carer burden questionnaires, the selection of research assessment measures, telehealth with advanced symptoms, dignity-conserving interventions, place of death in non-cancer conditions and evaluation of services. Each of these can shape clinical research studies and services in supportive and palliative care. Conclusions: Our commitment, complementary insights, backgrounds and methodological expertise were essential and productive. We continue to collaborate, developing high impact research, infrastructure and training and wider collaborations across Europe and beyond (PRISMA in palliative care, ENCCA in young people with cancer) across disciplines and professions in supportive and cancer survivorship care, palliative and end of life care.